Pengaruh Penerapan Model Pembelajaran Kooperatif TPS terhadap Hasil Belajar Matematika Peserta Didik - Syafa'atun Syafa'atun (Universitas Indraprasta PGRI, 2018)
Mathematics is general knowledge and must be mastered by every student. The general purpose of mathematics is to emphasize reasoning, the basis, and formation of students' attitudes to skills in applying mathematics. This study concerns the problem of the low value of mathematics learning outcomes of class VIII students at AT-TAQWA Middle School. This study, the learning model that wants to be explained to students is the Think Pair Share (TPS) learning model. This study used a quasi-experimental method with the Pre-Experiment Designs (no designs) design form. Respondents taken were eighth-grade students of AT-TAQWA Middle School, Central Jakarta in the 2013-2014 school year. During the study, the treatment was given 6 times. Obtained the highest score 88 lowest score 48. Average score 68.65. Median 68,875 Mode 69.5. The standard deviation of 10.26. And variance 113,19. It was concluded that the mathematics learning outcomes of students taught with Think Pair Share learning models were higher than the results of the mathematics learning of students taught by classical methods.